The Correlation Between Reading Comprehension and Vocabulary Mastery of Class XI Students at Madrasah Aliyah Al-Khairaat Ulatan - Fahrani, Fahrani; Afifah, Afifah; Zuhra, Zuhra; Suleman, Suleman (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
This study aims to investigate the relationship between the reading comprehension and vocabulary proficiency of students in the eleventh grade at Madrasah Aliyah Al-khairaat Ulatan. The research employs a quantitative approach with a correlational design, and the sampling method utilized is total sampling. The study includes 26 students from the eleventh-grade class at Madrasah Aliyah Al-khairaat Ulatan. The research instrument consists of a multiple-choice test, and data collection involves two types of tests: a reading comprehension test and a vocabulary mastery test, each comprising 10 questions. Data analysis was conducted manually using SPSS 25. The findings of the research reveal a significant correlation between reading comprehension and vocabulary mastery, with a two-tailed significance (Sig.) value of 0.007. The calculated correlation coefficient (r) is 0.518, indicating a strong correlation (greater than 0.5 but less than 0.75). The Pearson correlation coefficient of 1 signifies a positive correlation between the two variables. Therefore, the research concludes that the alternative hypothesis (Ha):